2023
DOI: 10.2215/cjn.0000000000000018
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Whole-Body Vibration on Gait Ability and Balance among Older Hemodialysis Patients

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 42 publications
(72 reference statements)
0
13
0
Order By: Relevance
“…The research team reported there were no serious adverse effects exhibited by the participants, "however, whole-body vibration did not improve gait ability and balance, as assessed by the physical performance tests." 1 The authors did point out that: Although there are few studies examining the efficacy of balance training in hemodialysis patients, Frih et al reported that a 24-week program with balance training (30 min/session) four times a week on nondialysis days improved the postural balance of hemodialysis patients when included in a usual endurance-resistance training monitored by profession balance of hemodialysis patients when included in a usual endurance-resistance training monitored by professional physiologists. 1 The results of this study indicate that if there are shortcuts to improving gait and balance in hemodialysis patients, the whole-body vibrator does not appear to be it.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The research team reported there were no serious adverse effects exhibited by the participants, "however, whole-body vibration did not improve gait ability and balance, as assessed by the physical performance tests." 1 The authors did point out that: Although there are few studies examining the efficacy of balance training in hemodialysis patients, Frih et al reported that a 24-week program with balance training (30 min/session) four times a week on nondialysis days improved the postural balance of hemodialysis patients when included in a usual endurance-resistance training monitored by profession balance of hemodialysis patients when included in a usual endurance-resistance training monitored by professional physiologists. 1 The results of this study indicate that if there are shortcuts to improving gait and balance in hemodialysis patients, the whole-body vibrator does not appear to be it.…”
mentioning
confidence: 99%
“…A team of researchers from Japan, writing an article published in this issue of CJASN , 1 noted “the incident rate of falls among hemodialysis patients is 1.18–1.60 per patient-year, which is much higher than that in the general older population (≥65 years), at approximately 0.67 per person-year.” 1…”
mentioning
confidence: 99%
See 3 more Smart Citations